Innovation in Development Administration : Using Technology to Enhance Transparency and Accountability - Wahyudi Mokobombang (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research examines innovations in development administration through the application of technology to enhance transparency and accountability in governance processes. Using a case study approach across three regional governments in Indonesia, the study analyzes the implementation of information and communication technologies (ICTs) in public administration systems. Data was collected through semi-structured interviews with 45 stakeholders, direct observations of e-governance platforms, and analysis of implementation reports. The findings reveal that strategic technology deployment can significantly improve communication channels between government and citizens, increase public participation in development processes, and strengthen accountability mechanisms. However, successful implementation depends on institutional readiness, human resource capacity, and appropriate regulatory frameworks. This research contributes to understanding how digital transformation can support good governance principles in developing contexts while highlighting implementation challenges that must be addressed for technology-driven administrative reforms to succeed.